The effects of Ni-addition on the crystal structure, thermal properties and morphology of Mg-based hydroxyapatites synthesized by a wet chemical method - Ince, Turan; Kaygili, Omer; Tatar, Cengiz; Bulut, Niyazi; Koytepe, Suleyman; Ates, Tankut (Elsevier Sci Ltd, 2018)
Four Mg-based hydroxyapatites (HAps) doped with Ni at various amounts of 0, 0.6, 1.2 and 1.8 at% were prepared at the temperature of 870 degrees C by a wet chemical synthesis. The crystallite size, lattice parameters and crystallinity percent dramatically decreased with adding of Ni. The amount of HAp phase for all the Ni-containing samples is smaller than that of the Ni-free MgHAp. Furthermore, the lattice strain, stress and anisotropic energy density values were affected by the amount of Ni. The differential thermal analysis (DTA) measurements taken in the temperature range from 25 to 1000 degrees C showed that all the samples are thermally stable. No significant change in the morphology was observed. It was observed that the gradual introduction of Ni caused the Ca-deficiency.
Keywords: Hydroxyapatite; Wet chemical method; X-ray diffraction (XRD); Morphology